Juntos Global: Deploying human centered design to motivate the newly banked - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2018)
The case is set in March 2018. Neha Bhatia Ramdas the Director of Sales at Juntos Global is visiting a prospective partner bank of her company in Singapore, which wants to expand its outreach amongst the unbanked population in South East Asia. The partner bank is not comfortable in sharing their customer data with Juntos, and Neha has been entrusted with the difficult task of convincing the partner bank to share their data with Juntos. Juntos specialises in deploying SMS based solutions powered by data analytics capabilities ifor financial service providers to help them serve their newly banked customers more efficiently. The Juntos SMS based platform helps the newly banked customers to build new habits like building formal savings habits through behavioural science strategies by building a relationship of ‘trust’ with their customers. By creating trusting relationships between financial service providers and their customers based on the principles of Human Centred Design (HCD), Juntos was able to generate measurable increases in account usage in many of their projects. The Juntos business model was a partnership model, wherein the partner financial service was equally involved in the implementation of the Juntos solution, especially in the beginning of the project. For monetisation, Juntos had an all-inclusive monthly subscription pricing mechanism based on the number of active users. Juntos used an agile implementation process that was preceded by a useful ethnographic study that allowed Juntos to customise their solution for their partner clients. Juntos typically implemented pilot projets with their partners, prior to implementing large scale projects. The flipside of this arrangement was the long sales cycle that was the primary impediment to Juntos success. Typically tedious and lengthy, the sales process often involved interactions with multiple business units in financial institutions and needed buy-in from all of them. Moreover, financial inclusion yielded small margins and therefore required scale. Given the need for scale to show measurable success in their pilot projects, and the long sales cycle of their projects, before the commencement of the pilot project implementation, the company was realising gradually that perhaps the strategy of preceding the actual implementation of projects with pilot projects was probably not a feasible solution. The case and teaching notes elaborates the problems related to financial exclusion and helps illustrate how behavioural economics and HCD could be used as tools for enhancing financial inclusion. The case also The case and teaching notes also helps highlight the need for financial inclusion and the inseparable link that exists between financial inclusion and social inclusion.